Perwersje archiwum - Gajewska, Agnieszka (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
Perversions of the archive In the article, the author discusses the problematic status of an archival document, taking into account the concepts of perverse historiography and the methodological indicators of the apartheid archive. Documents stored in IPN (Institute of National Remembrance) have been used to show the challenges faced by the people investigating the documents stored there and attempting to unify the material found in the archive. The analysis of Autor Solaris, a 2016 biographical documentary film about Stanisław Lem, is preceded by reflections on the involvement of the archive researchers in politics and their reproductions of clichés and stereotypes about the past, which the author sees as directly leading to blurring and erasing of the victims’ testimonies. In doing so, the author uses critical analyses of the pornographic aspects of the presentation of mass murder victims. Relating to a concept proposed by one of the critics indicating that using archival sources in modern art leads to a mass amnesia, the author points to the dangers of using Nazi propaganda films in contemporary documentary film.